TREATMENT OF GENITAL HERPES - Baratova M. R; Salamova L. A; Tilakobilov I. B; Oripov R. A (International Engineering Journal For Research & Development, 2021)
Genital herpes (GH) is one of the most socially significant problems in the clinical practice of dermatovenerologists, obstetricians, gynecologists, urologists. The number of patients with GH has increased by 30% over the past 10 years. The main role in the etiology of HSV belongs to HSV type 2 (HSV-2), but the pathogens of this pathology can become both HSV type 1 (HSV–1) and a combination of both types of herpes simplex virus. The prevalence of HSV-2 infection in the population ranges from 7 to 40% and averages 20%.